Parenting by Parents Who Work in Traditional Market, Perak District, Jombang Regency in the Perspectives of Law No. 23 of 2002 concerning Child Protection - Salwa Azyyati; Habibi Al Amin (JURNAL AKTA, 2024)
Children are a trust given by Allah, as a trust, the entrusted parents must take good care of their children by caring, nurturing, and providing everything that keeps the child cared for in accordance with the expectations of the trustee. The obligation of both parents to their children is what efforts must be made by parents in meeting the needs of children in all fields. Not only meeting physical needs, such as providing for food or daily meals, parents are also required to educate their children from an early age. In Indonesia, the obligations of parents to children have been regulated in Law No. 23 of 2002 in article 26 paragraph (1) stating that parents are obliged and responsible to nurture, maintain, educate, and protect children, grow and develop children in accordance with their interests and talents, prevent children from marrying at an early age, provide character education and instill children's ethical values. This research is a field research using an empirical juridical law approach with qualitative research methods. The results of the study stated that the parenting pattern of parents who work at the Perak Traditional Market Lapak, Perak District, Jombang Regency uses (1) the Perak Traditional Market Community or the Perak Village Community uses three democratic, authoritarian, and permissive parenting styles. And there are still many finding parenting patterns that are not appropriate because parents are less able to divide their time.